Seamlessly fused digital-analogue reconfigurable computing using memristors - Alexantrou Serb (Nature Portfolio, 2018)
Conventional analogue and digital circuits are mixed at signal level yet remain technologically separate, adding complexity and cost. This work introduces a new design paradigm where the analogue and digital worlds are seamlessly fused via memristors, enabling electronics with reconfigurability.